Achieving agility using business model stress testing - Harry Bouwman; Jukka Heikkilä; Marikka Heikkilä; Carlo Leopold; Timber Haaker (Springer, 2022)
Business Model (BM) Innovations aim at making systemic changes in the business logic of companies when they are bringing innovative products and services to the market. Companies should be sensitive to changes in their business environment and able to modify their BMs in an agile way. To assess the agility of BMI during specific market entry situations, this paper uses a method that stress tests the value proposition and the components of a BM against contingent uncertainties. We present three qualitative case studies of companies that differ in their market entry approach. Starting from their strategic orientation, these case companies’ stress test their Business models and BM components, using a scenario-based identification of uncertainties. The BM Stress Test method contributes to a quick understanding of the components their BM needs to monitor, reconsider, or improve. Such stress testing helps enhance business agility. The research contributes to market strategy and business modelling research by introducing BM Stress Testing as a new method that can achieve and maintain agility regarding BM uncertainties.